2018
DOI: 10.2478/pjst-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Profile of the Muscles of the Upper Limbs in Sport Climbers

Abstract: Introduction. Studies have demonstrated an important role of muscle strength and endurance in climbing. However, little research has explored the speed parameters of the muscles of climbers. This study aimed to evaluate biomechanical indices of the functional status of the upper limbs in climbers. Material and methods. Group G1 (n = 3) were athletes who were able to climb 8c+/9a climbing routes using the red-point style and 7c+/8b routes with the on-sight style. Group G2 (n = 5) comprised climbers who were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…As stated in the preceding section, this study was governed by the review of literature as the assessment of International journals relevant and comprehensive, like Q4 Scopus journal, Sport Discus, Google Scholar, Web of Science (WOS) de ISI Thomson Reuters, Latindex, Scopus, Scielo, Dialnet, and Google Books). Rock climbing movement was grouped into various positions, including the arm, the weight distribution between the arm and leg, foot position on the grip, posture with rock climbing board, install a safety position, and the position falls [35], [37]- [39]. The result of this stage in table 3 below (appendix 1).…”
Section: Resultsmentioning
confidence: 99%
“…As stated in the preceding section, this study was governed by the review of literature as the assessment of International journals relevant and comprehensive, like Q4 Scopus journal, Sport Discus, Google Scholar, Web of Science (WOS) de ISI Thomson Reuters, Latindex, Scopus, Scielo, Dialnet, and Google Books). Rock climbing movement was grouped into various positions, including the arm, the weight distribution between the arm and leg, foot position on the grip, posture with rock climbing board, install a safety position, and the position falls [35], [37]- [39]. The result of this stage in table 3 below (appendix 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the study of Fryer et al (8) showed higher MVC values in boulderers achieving 6B1 to 7B1 RP than in lead climbers reaching 7a1 to 8a RP (8). Both boulderers achieving $7B (22) and lead climbers (38) presented greater handgrip strength parameters than control subjects. Endurance characteristics of sport climbers and control subjects regarding climbing-specific endurance test (force time integral) and pull-ups are presented in Table 5.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the study of Fryer et al (8) showed higher MVC values in boulderers achieving 6B+ to 7B+ RP than in lead climbers reaching 7a+ to 8a RP ( 8 ). Both boulderers achieving ≥7B ( 22 ) and lead climbers ( 38 ) presented greater handgrip strength parameters than control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Maximal strength training to develop the high force capabilities of the shoulder adductors, forearm flexors, and synergistic musculature can be used. Training exercises such as the weighted pull-ups, bench press, machine-based variations (78), and weighted hang board training for the finger and forearm muscles are appropriate to improve their function (43). These exercises, when prescribed appropriately, share the common adaptation of increased neural drive and force production (1) (Table 4).…”
Section: Maximal Strengthmentioning
confidence: 99%
“…Force values in the region of 1000 N have been reported for dynamic jumping techniques used in speed climbing (14). Maximal strength training is designed to overload the following: the triple extension movement pattern seen during the ascent phase of speed climbing (34), the concentric pulling action of the shoulder adductors (78), and forearm flexor muscles responsible for gripping holds (90).…”
Section: Maximal Strengthmentioning
confidence: 99%